Hadis Nabi Dalam Pandangan Syaikh Muhammad Al-Ghazalī - Badri Khairuman (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2016)
In the development of the study of hadith, the scholars tend to focus on critical studies al-naqd sanad al-Hadith of the study of al-naqd al-matn al-Hadith. In contrast to the study of Hadith in the period companions, who are even more emphasis on the study of hadith matn. This is due to the rampant cases of forgery of hadith in the early days of Islam.Muhammad Ghazali was a Muslim scholar in Egypt among so many Muslim thinkers who try to assess traditions with emphasis on the study of the study matn sanad. Al Ghazali is not glued to the systematic rules sanad hadith validity but can be initiated by matn research traditions. In fact, it is not uncommon quality Ghazali rejected Hadith valid because it is not in accordance with the general principles of the teachings of the Quran and rational argument.Al-Ghazali then try to formulate some kaedah relating to the validity of matan hadith. As a result Ghazali sought in presenting his thoughts on the rules of hadith criticism matn philosophically interesting to observe. This article seeks to menegungkap how epistemological problems that need to be studied more in depth in the study of hadith. The purpose, to answer how the concept of analysis, methods and approaches offered Ghazali do with understanding Hadith